Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5455/ijmsph.2016.24012016345
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice toward MERS-CoV among primary health-care workers in Makkah Al-Mukarramah: an intervention study

Abstract: Background: Saudi Arabia (KSA) showed a higher number of Middle East respiratory syndrome-coronavirus (MERS-CoV) infection in Eastern Mediterranean Region. Satisfactory knowledge, positive attitude, and healthful practice of health-care workers (HCWs) regarding MERS-CoV are a cornerstone in prevention of virus spread and disease outbreak. Objective: To assess and improve knowledge, attitude, and practice (KAP) of HCWs toward MERS-CoV. Materials and Methods: An interventional prospective study was conducted dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 11 publications
(15 reference statements)
7
32
0
2
Order By: Relevance
“…Previous study indicated the importance of health education in improving knowledge, attitude and practice toward MERS infection in preventing the virus spread and disease outbreak. 23 The study showed that level of satisfactory knowledge, positive attitude, and good practice of studied health care workers significantly improved after exposure to educational program. 23 Another study recommended that courses on new emerging diseases, field epidemiology, and tropical medicine should be introduced to medical students to prepare them for dealing with these types of health emergencies.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous study indicated the importance of health education in improving knowledge, attitude and practice toward MERS infection in preventing the virus spread and disease outbreak. 23 The study showed that level of satisfactory knowledge, positive attitude, and good practice of studied health care workers significantly improved after exposure to educational program. 23 Another study recommended that courses on new emerging diseases, field epidemiology, and tropical medicine should be introduced to medical students to prepare them for dealing with these types of health emergencies.…”
Section: Discussionmentioning
confidence: 89%
“…23 The study showed that level of satisfactory knowledge, positive attitude, and good practice of studied health care workers significantly improved after exposure to educational program. 23 Another study recommended that courses on new emerging diseases, field epidemiology, and tropical medicine should be introduced to medical students to prepare them for dealing with these types of health emergencies. 24 The present study showed positive attitude of the students about the disease and there were significant differences among different specialties.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Various researchers had reported that an individual's level of KAP is linked to competent control and prevention of illness, response to medical treatment, and advancement of one's individual health [6][7][8][9]. KAP level at lower standard had been one of the foremost pointers of poor health, unproductive health care practice, the drop of the disease screening rate, and unrealistic preventive behavior toward various infections in various settings [10,11]. Similarly, reliability is similar with precision and shows the extent to which the measurement tool is reproducible by determining its internal consistency [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that nurses working with patients with SARS experienced psychological distress [8]. Moreover, 91.8% of healthcare providers in Saudi Arabia, nearly half of them nurses, were found to have a negative attitude toward treating patients with suspected or confirmed MERS [9]. As MERSrelated deaths began to be reported, levels of anxiety and stress increased, mainly because of the possibility of involuntary placement and dispatch to other front-line areas with a workforce shortage.…”
Section: Introductionmentioning
confidence: 99%